Modelling Dominant Factors of Technology Acceptance in Education: A Systematic Review Analysis of Indian Studies - Sharma, Pawan Kumar; Masih, Enid; Chauhan, Shanti Swaroop (Indian Journal of Educational Technology, 2024)
The study aims to identify common external factors of the Technology Acceptance Model (TAM) that influence the adoption of digital education in India. The analysis included a systematic review of 20 independent Indian research papers published in leading journals. This work summarizes existing knowledge in the areas of e-learning, m-learning, and learning management systems and their acceptance in education over the last decade. The results show that social influence, self-efficacy, result expectancy, content quality, and facilitating conditions are the most frequently used external factors. The strengths of the causal relationships between these 5 independent variables and the dependent variables of the main constructs of TAMs were developed into the conceptual model. India, with its diverse learning needs, is immensely benefiting from the latest advances in educational technologies. For effective implementation, it is important to understand how students and teachers in India perceive and use technology. The results of this study can help improve educational outcomes, benefiting not only India but also the global education community. The causal relationship developed serves as a reference for researchers working on educational technology and the further development of TAM.